2021
DOI: 10.1371/journal.pone.0247178
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of integrating survivors of stroke into cardiac rehabilitation: A mixed methods pilot study

Abstract: Background Survivors of stroke are often deconditioned and have limited opportunities for exercise post-rehabilitation. Cardiac Rehabilitation (CR), a structured exercise program offered post-cardiac event in the United States (U.S.), may provide an opportunity for continued exercise. The purpose of this study was to examine the feasibility of integrating survivors of stroke into an existing, hospital-based CR program through an assessment of (1) recruitment, uptake and retention, (2) adherence and fidelity, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 62 publications
2
12
1
Order By: Relevance
“…Overall, participants in this study identified that the cardiac rehabilitation programme helped them to make risk-reducing lifestyle changes in categories that included dietary changes, smoking cessation, mindfulness, and physical activity levels, similar to previous quantitative and qualitative findings where knowledge of risk-factor reduction was reinforced and/or learned in CR-based secondary prevention programmes [ 22 , 23 , 25 , 28 , 48 ]. Access to healthcare professionals for ongoing exercise and secondary prevention is a recurrent theme in the stroke literature [ 49 , 50 ], and cardiac rehabilitation may prove an important bridge to independent self-management of physical activity for secondary prevention after stroke.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Overall, participants in this study identified that the cardiac rehabilitation programme helped them to make risk-reducing lifestyle changes in categories that included dietary changes, smoking cessation, mindfulness, and physical activity levels, similar to previous quantitative and qualitative findings where knowledge of risk-factor reduction was reinforced and/or learned in CR-based secondary prevention programmes [ 22 , 23 , 25 , 28 , 48 ]. Access to healthcare professionals for ongoing exercise and secondary prevention is a recurrent theme in the stroke literature [ 49 , 50 ], and cardiac rehabilitation may prove an important bridge to independent self-management of physical activity for secondary prevention after stroke.…”
Section: Discussionsupporting
confidence: 77%
“…Exercise and lifestyle-based interventions modelled on cardiac rehabilitation (CR) have been proposed for physical conditioning to improve habitual PA for survivors of stroke and to reduce lifestyle risk factors after stroke [ 19 ]. CR is a proven and established secondary prevention programme in coronary heart disease [ 20 , 21 ], and results from across Europe and North America suggest that CR is not only feasible to provide after stroke, but it is a safe, effective, and integrated approach for risk-factor reduction and to improve cardiorespiratory fitness [ 4 , 22 , 23 , 24 , 25 ]. Notably, stroke participants are reported to make similar improvements to cardiac patients during CR in cardiorespiratory fitness; risk-factor reduction; and physiological markers, including lipid profiles and blood pressure [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations